Thermal behaviour studies of solid state compounds of cinnamylidenepyruvate with trivalent lanthanides and yttrium (III) in an atmosphere of CO2 - de Oliveira, José Dilson Silva; Fertonani, Fernando Luís; Melios, Cristo Bladimiros; Ionashiro, Massao (Eclética Química, 2002)
Solid state cinnamylidenepyruvate of trivalent lanthanides (except for promethium) and yttrium, were prepared. Thermogravimetry, derivative thermogravimetry (TG, DTG), differential scanning calorimetry (DSC), X-ray diffraction powder patterns and complexometry were used to characterize and to study the thermal behavior of these compounds in a dynamic CO2 atmosphere. The results obtained showed significative differences on the thermal stability and thermal decomposition of these compounds, with regard to the thermal behavior study in a dynamic air atmosphere.